Exercising workers' rights in algorithmic management systems: Lessons learned from the Glovo-Foodinho digital labour platform case - Claudio Agosti; Joanna Bronowicka; Alessandro Polidoro; Gaetano Priori (European Trade Union Institute (ETUI), 2023)
With the Platform Work Directive still under negotiation and the ETUC calling for an EU Directive on Algorithmic Systems at Work, groundbreaking research into the Spanish-Italian Glovo-Foodinho firm, a digital labour platform, has opened up an alternative path for workers wanting to scrutinize application and access their rights in digitalised workplaces, governed by algorithmic management. This involves close cooperation between trade unions, reverse engineering and Data protection authorities (DPA). As illustrated in this report, the current GDPR legislative framework has proven to be both robust and flexible. The report also reveals the details of the collaboration between ETUI and a technical team of experts led by Claudio Agosti into the so-called 'black box'. It details how the algorithmic management systems used by Foodinho, an Italian subsidiary of the Spanish food delivery company Glovo, works to control its workforce, namely: Tracking riders' location outside working hours. Sharing the location (both outside and during working hours), along with other personal data, with undisclosed third parties not mentioned in the app's documentation. Generating a score associated with the rider's personal profile, a value inconsistent with the documented 'Excellence Score' provided by Glovo-Foodinho: a hidden score. Background In 2019, algorithm analyst, Claudio Agosti, started to work with the ETUI Foresight Unit on research and training courses aimed at understanding the 'technicalities' behind Artificial Intelligence. Five years later, the ETUI is releasing a technical report which meticulously outlines the techniques used by researchers to observe the internal logic of the app used by riders in Italy and documents its actual behavior in terms of harvesting their personal data. The technical analysis was made in 2021-2022-2023, after Italian DPA, responsible for enforcing the EU's General Data Protection Regulation (GDPR) fined the company 2,600,000 euros in 2021 for failing to protect the digital rights of its workers. Glovo appealed. They did not pay the fine and as released in this report, they have continued the same unregular practices. Finally, these new evidences have been reported to the Italian DPA. New challenges for workers' rights According to the authors of this ETUI report, collecting evidence about algorithmic management is critical for workers seeking to enforce their rights by filing complaints with national DPAs or the competent courts. The availability of technical expertise can also help improve workers' negotiating positions in a collective bargaining context. 'Ultimately, we believe that, by helping workers understand the apps that control them, we can give them the key to unlocking their rights, thus building a fairer future of work for all.'
Keywords: 330